A rare finding of left innominate artery arising from the left pulmonary artery in a case of tetralogy of fallot - Bakthavachalam, Vigneshwar; Vaidyanathan, Swaminathan (International Surgery Journal, 2023)
Right-sided aortic arch with an aberrant left innominate artery arising from the left pulmonary artery is a very rare finding in the tetralogy of fallot (TOF). A 2-year-old boy presented for routine intracardiac repair of TOF. A routine angiogram raised suspicion of the left innominate artery with abnormal origin. 640-slice CT was done to delineate the anatomy. The left innominate artery was re-implanted in the descending aorta and the intracardiac repair was performed.